2021
DOI: 10.3389/fsurg.2021.671403
|View full text |Cite
|
Sign up to set email alerts
|

The Global Research Trends and Hotspots on Developmental Dysplasia of the Hip: A Bibliometric and Visualized Study

Abstract: Background: Developmental dysplasia of the hip (DDH) is a common musculoskeletal disorder in newborns and also one of the most common causes of hip arthritis in women. Many topics concerning DDH still remain controversial, and the global research trend in this field has not been well-studied yet. The aim of the present study was to illustrate the overall knowledge structure, development trends, and research hotspots of DDH.Methods: The publications related to DDH from 1998 to 2020 were identified from the Web … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 57 publications
(78 reference statements)
0
17
0
1
Order By: Relevance
“…Of note, these journals share common features, that are high IF. It is generally known that journals with high IF are attracted by scholars in selecting for publishing their high-quality studies, while these papers, in turn bring more citations for journals to further improve their influence ( Wu et al, 2021c ; Zhang et al, 2022a ; Shen et al, 2022b ). From the perspective of national distribution of these journals, we have found that there were very few influential journals from East Asia, despite Eastern Asian countries such as China, Japan and South Korea were all the major contributors to this field.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these journals share common features, that are high IF. It is generally known that journals with high IF are attracted by scholars in selecting for publishing their high-quality studies, while these papers, in turn bring more citations for journals to further improve their influence ( Wu et al, 2021c ; Zhang et al, 2022a ; Shen et al, 2022b ). From the perspective of national distribution of these journals, we have found that there were very few influential journals from East Asia, despite Eastern Asian countries such as China, Japan and South Korea were all the major contributors to this field.…”
Section: Discussionmentioning
confidence: 99%
“…The betweenness centrality (BC) is an indicator of a node’s centrality, which can reflect the importance of nodes within the networks. Generally, nodes with a BC value of more than 0.1 occupy the pivotal positions connecting a large number of nodes, and usually identified as hubs nodes displayed in purple rings ( 46 ). In co-cited author network analysis, Mani Menon, Ficarra V, and Tewari Ashutosh K were the top 3 with the highest citations.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Several free visualization tools, including VoSviewer, 14 CiteSpace, 15 and BibExcel, 16 enable researchers to create knowledge structure maps and track scientific developments. As a result, bibliometric analysis has become an increasingly popular method to obtain the knowledge structure and current research hotspots in a field, and currently widely used in orthopedic diseases and surgical methods, such as spinal stenosis, 17 developmental hip dysplasia, 18 knee osteoarthritis, 19 spinal deformity 20 and atlantoaxial surgery, 21 etc. Since entering the 21 st century, MISS has received extensive attention and research, and major breakthroughs have been made in its surgical technology and technical skills.…”
Section: Introductionmentioning
confidence: 99%